PROGRAM PENINGKATAN KOMPETENSI PROFESIONAL GURU DI PONDOK PESANTREN DARUSSALAM KASOMALANG, SUBANG - Syarifah; Ihwan Mahmudi; Saiful Anwar; Samsirin; Nurul Azizah; Haniatul Mabruroh; Halida Umami; Nurul Salis Al Amin (LPPM STAI Muhammadiyah Probolinggo, 2025)
Teacher professional competency improvement programs have a significant impact on the development of students as individuals, especially during critical developmental stages. Thus, instruction to improve teachers' professional competency in character development for students at the Darussalam Kasomalang Islamic Boarding School in Subang. Focusing on teachers' skills in recognizing and selecting effective tactics, particularly in character development in the classroom, this training combined theoretical and practical approaches. Following the workshop, participants and presenters engaged in a discussion and question-and-answer session. Based on the positive and satisfying responses from teachers during the training and the question-and-answer session, the results showed significant improvement. According to the program review, this improvement was largely driven by the performance of the facilitators and the materials they used. Future iterations of the course could benefit from the recommendations made for facilitator training, training evaluation, and the creation of additional materials.